Sector Financial Performance Analysis with Integrated SOWIA-ELECTRE III Methods: The Case of Turkish Real Sector - Z. Şenol; S. Şener; T. Gülcemal (Финансы: теория и практика)
The aim of this study is to determine the financial performance of the corporate sector employing the integrated SOWIA-ELECTRE III method. In this framework, the data of 10 real sectors operating in Borsa Istanbul over the period 2016–2022 are utilized. It was observed that the financial performance indicators affecting the sector performance varied over the years and that current liability rate, price to earning ratio, firm value/EBITA and return on equity ratios were important determinants of financial performance. According to the results of the performance rankings of the sectors obtained by the ELECTRE III method, it is understood that the highest performance was realized by retail trade in 2017, 2018, 2019, 2021 and 2022, construction and public works in 2016 and food, beverage and tobacco in 2020. In addition, the study compared sector performance rankings with sector index return rankings and the degree of the relationship was determined by the Spearman’s rank correlation coefficient. Accordingly, the correlation coefficients are positive, high and significant in 2017 and 2018. Accordingly, it can be said that there is a partial relationship between sector performances and sector returns. The study results show that portfolio managers and investors should give importance to financial performance analysis when making sector analysis, and economic managers that general economic conditions are important determinants in the development of sectors.